Capuchin monkey biogeography: understanding Sapajus Pleistocene range expansion and the current sympatry between Cebus and Sapajus. (29th January 2017) - Lima, Marcela G. M.; Buckner, Janet C.; Silva‐Júnior, José de Sousa e; Aleixo, Alexandre; Martins, Amely B.; Boubli, Jean P.; Link, Andrés; Farias, Izeni P.; da Silva, Maria Nazareth; Röhe, Fabio; Queiroz, Helder; Chiou, Kenneth L.; et al.
Abstract: Aim: Our aim was to examine gracile capuchin ( Cebus ) and robust capuchin monkey ( Sapajus ) diversification, with a focus on recent Sapajus expansion within Amazonia. We wanted to reconstruct the biogeographical history of the clade using statistical methods that model lineages' occupation of different regions over time in order to evaluate recently proposed 'Out of Amazonia' and 'Reinvasion of Amazonia' hypotheses as alternative explanations for the extensive geographical overlap between reciprocally monophyletic gracile ( Cebus ) and robust ( Sapajus ) capuchin monkeys. Location: Central and South America. Methods: We reconstructed a time‐calibrated molecular phylogeny for capuchins under Bayesian inference from three mitochondrial genes. We then categorized 12 capuchin clades across four Neotropical centres of endemism and reconstructed the biogeographical history of the capuchin radiation using six models implemented in 'BioGeoBEARS'. We performed a phylogeographical analysis for a robust capuchin clade that spans the Atlantic Forest, Cerrado, Caatinga and Amazonia. Results: We find support for a late Miocene vicariant Cebus‐Sapajus divergence and a Pleistocene Sapajus invasion of Amazonia from the Atlantic Forest. Our new analyses confirm Sapajus diversified first in the Atlantic Forest, with subsequent range expansion into widespread sympatry with Cebus in Amazonia, as well as multiple expansions into drier savanna‐like habitats. We do not find mitochondrial molecular congruence with morphological species distinctions for Sapajus flavius, S. cay, S. macrocephalus, S. libidinosus and S. apella ; instead, these five morphological types together form a single widespread clade (Bayesian posterior probability = 1) with geographical substructure and shared ancestry during the Pleistocene. Main conclusions: Our results support vicariance dividing ancestral capuchin populations in Amazonia versus the Atlantic Forest, and a Pleistocene 'Amazonian invasion' by Sapajus to explain the present‐day sympatry of Cebus and Sapajus .